Soybean Meal-Induced Intestinal Inflammation in Zebrafish Is T Cell-Dependent and Has a Th17 Cytokine Profile - Coronado, Maximo; Solis, Camila J.; Hernandez, Pedro P.; Feijóo, Carmen G. (Frontiers in Immunology, 2019)
Currently, inflammatory bowel disease is a serious public health problem on the rise worldwide. In this work, we utilized the zebrafish to introduce a new model of intestinal inflammation triggered by food intake. Taking advantage of the translucency of the larvae and the availability of transgenic zebrafish lines with fluorescently labelled macrophages, neutrophils or lymphocytes, we studied the behavior of these cell types in vivo during the course of inflammation. We established two feeding strategies, the first using fish that were not previously exposed to food (naïve strategy) and the second in which fish were initially exposed to normal food (developed strategy). In both strategies, we analyzed the effect of subsequent intake of a control or a soybean meal diet. Our results showed increased numbers of innate immune cells in the gut in both the naïve or developed protocols. Likewise, macrophages underwent drastic morphological changes after feeding, switching from a small and rounded contour to a larger and dendritic shape. Lymphocytes colonized the intestine as early as 5 days post fertilization and increased in numbers during the inflammatory process. Gene expression analysis indicated that lymphocytes present in the intestine correspond CD4+ T cells. Interestingly, control diet only induced a Treg profile in the developed model. On the contrary, soybean meal diet induced a Th17 response both in naïve and developed model. When feeding was performed in Rag1-/- fish, intestinal inflammation is not induced indicating that the process induced by soybean meal is T cell dependent.